The Urgency of Sharia Economic Regulation to Enhance Indonesia’s Economic Growth - Ima Ridhoatu Shofa (International Journal of Sociology of Religion, 2025)
Sharia economic regulation has an important role in encouraging Indonesia's economic growth, given the sector's great potential in strengthening financial inclusion, halal industry development, and improving social welfare. However, fragmented regulatory constraints and incompatibility with sharia principles hinder the development of the sharia economic sector. This research aims to identify the urgency of more comprehensive sharia economic regulation to support Indonesia's economic growth. The method used in this study is a normative juridical approach with an analysis of existing regulations and an empirical approach to assess the implementation of regulations in the field. The findings of the study show that more integrated regulations in accordance with sharia principles can increase Indonesia's competitiveness in the global market, expand financial inclusion, and develop the halal industry sector. In conclusion, strong and well-coordinated regulations in the sharia economic sector will accelerate Indonesia's economic growth by creating social justice and more optimal resource management.